Анализа укорељености нивоа серумског ПАЦАП-38, Фибулин-3 и ТЕМ1 са срчаном функцијом и прогнозом код пацијената са хроничном срчаном инсуфицијенцијом: Нивои серума ПАКАП-38, Фибулин-3 и ТЕМ1 код хроничне срчане инсуфицијенције - Chen, Yan; Zeng, Fanlong; Gao, Tianyun; Hu, Bayi; Zhang, Mo; Yu, Zongliang (Journal of Medical Biochemistry, 2025)
Objective: To analyze the relationships between the levels of serum fibrinum-3 (Fibulin-3), antihuman tumor endothelial marker 1 (TEM1), and pituitary adenylate cyclase-activating polypeptide-38 (PACAP-38) in elderly chronic heart failure (CHF) patients and classification of cardiac function and a negative prognosis.Methods: A total of 132 elderly CHF patients who were admitted to the hospital between July 2022 and July 2024 were chosen as the elderly CHF group, and 132 healthy people who were examined in the hospital during that time were chosen as the control group. According to the cardiac function classification criteria of the New York Heart Association (NYHA), Grade II (42 patients), Grade III (51 patients), and Grade IV (39 patients) groups were created from the elderly CHF patients. Based on whether MACE happened after discharge, elderly CHF patients were split into two groups: those who experienced MACE and those who did not. The levels of serum Fibulin-3, TEM1 and PACAP-38 in all the subjects were detected via ELISA. Serum Fibulin-3, TEM1, and PACAP-38 levels were correlated with cardiac function categorization in older CHF patients using Spearman correlation analysis.  Older patients with CHF had their MACEs examined using multivariate logistic regression analysis. Serum Fibulin-3, TEM1, and PACAP-38 were evaluated for their predictive value of MACEs in older individuals with CHF.Results: While the elderly CHF group's serum levels of Fibulin-3 and PACAP-38 were lower than those of the control group, their serum levels of TEM1 were higher.  P Grade III > Grade IV. Spearman correlation analysis revealed that there was a favorable correlation between the serum TEM1 level and the heart function classification of elderly CHF patients (rs=0.488, P